2014
DOI: 10.1039/c4sm00664j
|View full text |Cite
|
Sign up to set email alerts
|

Self-organizing microfluidic crystals

Abstract: We consider how to design a microfluidic system in which suspended particles spontaneously order into flowing crystals when driven by external pressure. Via theory and numerics, we find that particle-particle hydrodynamic interactions drive self-organization under suitable conditions of particle morphology and geometric confinement. Small clusters of asymmetric "tadpole" particles, strongly confined in one direction and weakly confined in another, spontaneously order in a direction perpendicular to the externa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 41 publications
(63 reference statements)
0
25
0
Order By: Relevance
“…While drag forces in complex media are important for microrheological applications, the out-of-equilibrium interactions between particles are also of interest for their potential to produce self-assembly [10]. The equilibrium interactions between colloidal particles are well understood, particularly in dilute suspensions; these include effects such as the wellcharacterized "depletion" interaction, and associated selfassembly phenomena [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…While drag forces in complex media are important for microrheological applications, the out-of-equilibrium interactions between particles are also of interest for their potential to produce self-assembly [10]. The equilibrium interactions between colloidal particles are well understood, particularly in dilute suspensions; these include effects such as the wellcharacterized "depletion" interaction, and associated selfassembly phenomena [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the most widely used are rod-shaped particles, including gold nanorods (Gu et al, 2012, 2011; Neupane et al, 2016; Chaudhari and Pradeep, 2014; Xiao et al, 2011a), colloidal ellipsoids (Han et al, 2006; Mukhija and Solomon, 2007), quantum rods (Tsay et al, 2006; Ohmachi et al, 2012), filamentous viruses (Lettinga et al, 2005), and dumbbell particles (Uspal et al, 2013; Uspal and Doyle, 2014), Typically, the rotation of rod-shaped imaging probes can be measured along two of the three possible rotational axes: in-plane rotational angle φ and out-of-plane rotational angle θ (Fig. 1a) (Anthony and Yu, 2015).…”
Section: General Methods For Probing Rotational Dynamicsmentioning
confidence: 99%
“…The three-dimensional orientation and position of the μm-sized rods suspended in viscous solutions was directly visualized by using conventional confocal fluorescence microscopy. Uspal et al (2013) and Uspal and Doyle (2014) synthesized dumbbell-shaped particles using continuous flow lithography and studied how the orientation of these particles affected their translational motion in microfluidic flows. They observed that tadpole-shaped particles with one large lobe and one small lobe quickly rotate to align with the direction of flow, whereas symmetric particles orient at random and oscillate transversely in the flow.…”
Section: General Methods For Probing Rotational Dynamicsmentioning
confidence: 99%
“…[18] identified ring-shaped particles which do not tumble in shear flow, in contrast to the tumbling behavior of axisymmetric particles reported by numerous earlier works; the particle shapes were derived as perturbations to a circular shape to obtain zero torques on the particle. Recent advances [19] have established self-aligning and centreline-focusing characteristics of asymmetric particles in Hele-Shaw flow -specifically, "dumbbell" and "trumbbell" shapes. Furthermore, modern fabrication techniques [20,21,22] allow for scalable fabrication of arbitrary-shaped microparticles, presenting an abundant landscape for the design of customized application-specific microparticles.…”
Section: Introductionmentioning
confidence: 99%